Effect of MWCNT carboxylation on mechanical, thermal and morphological behaviour of phenol formaldehyde nanocomposites. (April 2021) - Ravindran, Lakshmipriya; Sreekala, MS; Anilkumar, S; Thomas, Sabu
Phenol-formaldehyde resin is an inevitable polymer material because of their excellent properties like heat resistance, chemical resistance, creep resistance, and low water sorption. But the drawback associated with PF matrix is buckling and brittleness. The incorporation of nanofillers can effectively reduce these problems. Carbon nanotubes is one among the nanofiller which is widely used to enhance the mechanical, thermal, electrical properties of the host matrix.The present study deals with the synthesis and comparison of two Phenol-formaldehyde nanocomposites incorporated with pristine multiwalled carbon nanotubes and carboxylated multiwalled carbon nanotubes via in-situ polymerisation technique. The effect of filler loading (MWCNT, MWCNT-COOH) with different weight percentages (0.05 wt%, 0.08 wt%, 0.12 wt%, 0.15 wt%) has been investigated in this study. Pristine MWCNT was functionalised with carboxyl groups and confirmed by XRD, FT-IR, CHN analysis, X-ray photoelectron spectroscopy, AFM and Raman spectra. All these analysis showed successful funtionalisation of pure MWCNT. The prepared nanocomposites were compared by mechanical, thermal and morphological analysis. The effect of both fillers on tensile strength, stress-strain, young's modulus and elongation at break were also analysed. The addition of MWCNT and MWCNT-COOH have enhanced the mechanical and thermal properties of the prepared nanocomposite. The mechanical properties of PF-MWCNT nanocomposite showed a maxima for 0.12 wt% and for PF-MWCNTCOOH nanocomposite it was 0.08 wt%. Higher thermal stability was exhibited for 0.15 wt% MWCNT loading. The thermal stability enhanced by the addition of MWCNT COOH upto 0.12 wt% and then declined. Moreover the prepared nanocomposites were morphologically characterized by scanning electron microscope (SEM) and transmission electron microscope (TEM) and from the fracture analysis it is clear that the reinforcements brought plastic deformation of phenol-formaldehyde nanocomposite from brittle to more ductile material. From the TEM image it was clear that the presence of carboxyl groups attached on MWCNT reduced agglomeration in PF matrix. Halpin-Tsai modelling was done for comparing experimental and theoretical values of tensile modulus and it illustrates good correlation.